Liquid crystal phosphazenes - Davarci, Derya; Doganci, Erdinc (Elsevier, 2022)
In this review we highlight the publications about liquid crystal phosphazene derivatives. While some of the reports investigate of the liquid crystallinity of cyclic phosphazene derivatives, some of them are about phosphazene-based polymeric liquid crystal materials. Literature about liquid crystal phosphazenes were reviewed and their mesomorphic behavior were summarized. (C) 2022 Elsevier B.V. All rights reserved.
Keywords: Phosphazenes; Liquid crystal; Mesomorphism; Phase transition